Origem de capital e acesso aos incentivos fiscais e financeiros à inovaç\~ao no Brasil - Graziela Ferrero Zucoloto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper analyses Brazilian innovation polices, focusing on the access of subsidiaries and national enterprises to selected public innovation instruments: subvention, credit and Law 11.196/05. It presents theoretical aspects of government incentives to innovation; international experiences; the evolution of S&T&I Brazilian policies; fiscal and financial instruments related to business innovation and, at least, discusses the access of Brazilian enterprises to these instruments, by origin of capital.
Keywords: O38; 330; technological innovation; origin of capital; fiscal incentives; financial incentives; multinational enterprises; Innovationspolitik; Risikokapital; Brasilien